Self-reported continuing professional development needs of medical laboratory professionals in Ghana - Mainprice Akuoko Essuman; Nii Armah Addy; Samuel Essien-Baidoo; Irene Esi Donkoh; Felix A. Botchway; Justice Afrifa; Prince Agyeman; Leticia Awontayami Amaama; Samuel Amoah; Felix B. K. Sorvor; Richard K. D. Ephraim (Human Resources for Health, 2023)
Abstract Background Because of the essential nature of the work of medical laboratory professionals, continuing development in knowledge and skills is indispensable. The study aimed at identifying and prioritizing the development and training needs of medical laboratory professionals in Ghana. This is expected to help in developing focused continuing professional development (CPD) that meets the needs of practitioners as well as the changing medical trends. Methods An online cross-sectional survey in February 2022 using a structured questionnaire was conducted. Respondents were asked questions that collected demographic and work-related data about them, their participation, preference, and challenges in being part of CPDs. Finally, a list of topics based on (i) quality management systems, (ii) technical competence, (iii) laboratory management, leadership, and coaching, (iv) pathophysiology, and (iv) data interpretation and research were asked with the option to rate them on a 3-point scale (most, moderate, and least) in order of importance. Results A total of 316 medical laboratory professionals participated in the study. Overall, the most frequently selected topics for training based on domains for CPD training and ranking as most important were (i) quality management systems, (mean = 80.59 ± 9.024; 95% CI = 73.04–88.13); (ii) pathophysiology, data interpretation, and research (mean = 78.0 ± 6.973; 95% CI = 73.97–82.03); (iii) technical competence (mean = 73.97 ± 10.65; 95% CI = 66.35–81.59); and (iv) laboratory management, leadership, and coaching (mean = 72.82 ± 9.719; 95% CI = 67.44–78.2). The factors affecting the choice of training needs included the medical laboratory professionals’ current place of work, years in service, the reason for attending CPD activities, the period for attending the last CPD, being in a supervisory role, and the number of staff being supervised. Face-to-face presentations, training workshops, and hands-on workshops were the most preferred modes of CPD delivery with financial implications and workload/time constraints being the main challenges impeding CPD participation. Conclusion The identified needs will help in developing CPD programs that address what medical laboratory professionals prioritize as training needs. Stakeholders should incorporate these training needs into future programs and address the challenges highlighted in this study to have more relevant training for medical laboratory professionals.